Facilitating Systems Thinking Through Arts-Based STEM Integration - Danielson, Robert William; Grace, Elizabeth; White, Alison Joanne; Kelton, Molly Louise; Owen, Jeb P.; Saba Fisher, Kristin; Diaz Martinez, AnaMaria; Mozo, Maria (Frontiers in Education, 2022)
Engaging with socio-scientific issues often involves making sense of how - and for whom - actions, choices, and policies might affect aspects of daily life. Understanding the complexity of socio-scientific issues also requires recognizing the interconnectedness of - and working across - multiple communities and professions. We suggest that art, whether musical composition, illustrations, or sculpture / collage across materials would promote the synthesis of different types of knowledge across different scales and systems. The present investigation seeks to understand how arts integration into STEM curriculum could support systems thinking around socio-scientific issues, specifically around the issue of infectious pathogen transmission in rural-agricultural communities. Our after-school program, which works with 3rd – 5th grade students in rural-agricultural communities, leverages the arts to promote systems-level understanding of zoonotic diseases and ecosystem dynamics. A total of 23 students across two sites located in rural communities in the Western United States participated in our afterschool program. We found that after completing the program students expanded their understanding of both the connections between concepts and an understanding of careers related to ecosystem dynamics. We suggest that educators can integrate both arts and sciences together to enhance systems thinking and expand student perception of the interconnectedness of STEM disciplines and their everyday lives.